Does Tourism Change Tourist Attitudes (Prejudice and Stereotype) towards Local People? - Çelik, Sedat (VYSOKA SKOLA OBCHODNI & PRAZE, 2019)
The main goal of this study is to determine whether attitudes (prejudices and stereotypes) of domestic tourists towards South-easterners change after their travel experiences. Additionally, whether the levels of contact (the number of overnights stay, travel type, the number of arrivals at destination) with the local people have any effects on changes of attitude was determined to be sub-goals of this study. In this study, quantitative data analysis method was used. The research was designed as a non-experimental mixed pattern. The pre-holiday and post-holiday attitudes of domestic tourists arriving in Gaziantep and Sanliurfa were investigated using the questionnaire (n: 386). Additionally, data was gathered during the process of study from people who have never visited the Southeast to create a comparison group (n: 252). Factors analysis, frequency, ANOVA and t-test analyses were applied to the gathered data. As a result of analyses, the prejudices of participants who have never come to the Southeast have been higher. Also, positive changes were determined in the attitudes (prejudices, positive attitudes) of people who have undergone experiences of travel. However, it was also revealed that there are no statistically significant differences that are dependent on factors of contact variables (namely the type of travel, the number of overnights stays, and the number of arrivals at the destination). This research is important as it contributes to the gap in the tourism and social psychological area and explains the attitudes of tourists towards the local people. This research is also important in establishing whether tourism can be used as a tool for decreasing intercommunal problems.
Keywords: Tourism; Peace; Prejudice; Stereotype; Attitude Changes